Neurosteroids and their receptors in ischemic stroke: From molecular mechanisms to therapeutic opportunities. (October 2020) - Vahidinia, Zeinab; Karimian, Mohammad; Joghataei, Mohammad Taghi
Graphical abstract: Abstract: Extensive progress has been made to understand the pathophysiology of stroke but it is still a major cause of mortality and disability worldwide. There are few strategies for the treatment of this disease and the use of thrombolytic tissue plasminogen activator is limited due to the narrow time window. However, the administration of neuroactive steroids could be considered as a potential treatment approach to decrease ischemia-induced lesions. Neurosteroids receptors play important roles in neuroprotection mediated by these hormones. Membrane and intracellular receptors are both involved in the protective effects of estrogen and progesterone on ischemic brain injury. The intracellular receptors often regulate the gene transcription while the membrane receptors act through modulation of signal transduction pathways. Besides, allopregnanolone acts as a potent positive modulator of the GABA receptor. Moreover, the neuroprotective effects of vitamin D and dehydroepiandrosterone (DHEA) are mediated through the binding to vitamin D receptor (VDR) and several intracellular and membrane receptors, respectively. Activation of VDR could affect various processes including apoptosis, calcium metabolism, oxidative stress, immune modulation, inflammation and detoxification, and DHEA can modulate neurogenesis, neuronal function, and mitochondrial oxidative capacity. The present study aimed to describe the neuroprotective roles of the aforementioned neurosteroids with a focus on their receptors against ischemic stroke.